Co-host ncRNA MIR503HG/miR-503-5p antagonistically interfere with the crosstalk between fibroblasts and microvascular endothelial cells by affecting the production of LMW FGF2 in pterygium - Yue-Qi Yuan; Xing-Yuan Yan; Fang Zheng; Ming Yan (International Journal of Ophthalmology)
AIM: To explore the effect of co-host non-coding RNA (ncRNA) MIR503HG/miR-503-5p on the angiogenesis of pterygium. METHODS: MIR503HG/miR-503-5p/fibroblast growth factor 2 (FGF2) expression levels in pterygium tissues, control conjunctival tissues, and human pterygium fibroblasts (HPF) were examined by reverse transcription-polymerase chain reaction (qRT-PCR) and immunohistochemical methods. Effects of MIR503HG/miR-503-5p on low molecular weight FGF2 (LWM FGF2), migration and angiogenesis of human retinal microvascular endothelial cells (HRMEC) were determined in an HPF and HRMEC co-culture model using Western blots, wound healing assay, Matrigel-based tube formation assay, and Transwell assay. RESULTS: MIR503HG/miR-503-5p/FGF2 pathway was actively increased in pterygium tissue and there was a negative correlation between the expression of the two ncRNAs. FGF2 expression level was positively correlated with MIR503HG and negatively correlated with miR-503-5p. Overexpressed MIR503HG/miR-503-5p did not affect the migration and angiogenesis of HRMECs cultured separately, but significantly affected migration and angiogenesis of HRMEC in HPF and HRMEC co-culture models. Western blotting revealed that MIR503HG/miR-503-5p overexpression significantly increased LMW FGF2 expression in HPF. CONCLUSION: MIR503HG/miR-503-5p inhibits HRMEC migration and angiogenic function by interfering with the interaction between HPF and endothelial cells via reducing LMW FGF2 in HPF.